Two Case Reports of Madelungûs Disease: CT Finding. - Buranachokpaisan, Chanpen (The ASEAN Journal of Radiology, 2019)
Madelungûs disease or Benign symmetric lipomatosis is the rare disease that is the one of differential diagnosis of palpable neck mass that easily diagnosis by CT imaging. We report two cases of this condition and review the radiological findings.